Contesting Da’wah Authority in Indonesian Mosques and Islamic Organizations - Saifuddin, Saifuddin; Mubasyaroh, Mubasyaroh; Masdi, Masdi (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
In the process of segregation, every social institution, including religious ones, experiences both conflict and integration, as well as consensus and contestation. As a religious social institution, the mosque serves as a place for prostration in mahdhah worship and as a center for community development. This article examines two critical issues: first, the shifting dynamics of the mosque’s function as a social institution in Islamic preaching, and second, the negotiation and contestation of Islamic preaching spaces between mosques and other Islamic mass organizations. Employing a qualitative approach, this study conducts an in-depth analysis of primary data sources. Key insights were gathered through participatory observation of behavioral processes and activities within the research context.The research conducted in Kudus revealed several key findings: First, as a site for disseminating Islamic values, mosques serve as a vital medium for employing diverse preaching methods. Second, the overlapping social roles shared with other institutions have led to struggles, shifts, and even takeovers of functions traditionally held by religious organizations—including mosques. Consequently, mosques have transformed into contested arenas for political piety.